Magnesium Restores Activity to Peripheral Blood Cells in a Patient With Functionally Impaired Interleukin-2-Inducible T Cell Kinase - Howe, Matthew K.; Dowdell, Kennichi; Roy, Amitava; Niemela, Julie E.; Wilson, Wyndham; McElwee, Joshua J.; Hughes, Jason D.; Cohen, Jeffrey I. (Frontiers in Immunology, 2019)
Interleukin-2-inducible T cell kinase (ITK) is critical for T cell signaling and cytotoxicity, and control of Epstein-Barr virus (EBV). We identified a patient with a novel homozygous missense mutation (D540N) in a highly conserved residue in the kinase domain of ITK who presented with EBV-positive lymphomatoid granulomatosis. She was treated with interferon and chemotherapy and her disease went into remission; however, she has persistent elevation of EBV DNA in the blood, low CD4 T cells, low NK cells, and nearly absent iNKT cells. Molecular modeling predicts that the mutation increases the flexibility of the ITK kinase domain impairing phosphorylation of the protein. Stimulation of her T cells resulted in reduced phosphorylation of ITK, PLCγ, and PKC. The CD8 T cells were moderately impaired for cytotoxicity and degranulation. Importantly, addition of magnesium to her CD8 T cells in vitro restored cytotoxicity and degranulation to levels similar to controls. Supplemental magnesium in patients with mutations in another protein important for T cell signaling, MAGT1, was reported to restore EBV-specific cytotoxicity. Our findings highlight the critical role of ITK for T cell activation and suggest the potential for supplemental magnesium to treat patients with ITK deficiency.